2000
DOI: 10.1006/ccog.1999.0412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Conditioning Is Pavlovian Conditioning: Issues of Definition, Measurement, and the Theoretical Importance of Contingency Awareness

Abstract: In her commentary of Field (1999), Hammerl (1999) has drawn attention to several interesting points concerning the issue of contingency awareness in evaluative conditioning. First, she comments on several contentious issues arising from Field's review of the evaluative conditioning literature, second she critiques the data from his pilot study and finally she argues the case that EC is a distinct form of conditioning that can occur in the absence of contingency awareness. With reference to these criticisms, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…First, there is evidence from Pavlovian conditioning that effects such as conditioning without contingency awareness and resistance to extinction that are argued to be unique to EC can be found when the learning episode has ecological relevance (Field, 2000a). This leads to the idea that EC will be strongest when the CS and US make conceptual sense (Field, 2000a(Field, , 2001. Similarly, De Houwer et al suggested that 'belongingness' between the CS and US might be an important moderator of EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is evidence from Pavlovian conditioning that effects such as conditioning without contingency awareness and resistance to extinction that are argued to be unique to EC can be found when the learning episode has ecological relevance (Field, 2000a). This leads to the idea that EC will be strongest when the CS and US make conceptual sense (Field, 2000a(Field, , 2001. Similarly, De Houwer et al suggested that 'belongingness' between the CS and US might be an important moderator of EC.…”
Section: Discussionmentioning
confidence: 99%
“…One solution is to look not at visual similarity, but conceptual similarity. Field (2000a) has argued that EC should occur (or at least be stronger) in CS-US pairings that have an obvious conceptual connection for the participant. This idea is consistent with Davey's (1994) suggestion that the mechanism underlying evaluative conditioning is a conceptual transfer between the CS and US.…”
Section: Conceptual Similarity Between the Cs And Usmentioning
confidence: 99%
“…One view put forward by Field (2000aField ( , 2000b was that most studies in evaluative learning have not successfully demonstrated a dissociation or even associative learning at all due to several problems of measurement: (1) neutral and affective stimuli are not paired on a random basis but on perceptual similarity, hence the results can be understood within a visual categorization or concept learning framework; (2) only a within-subjects control condition is used (where the control stimuli consist of two neutral pairs); and (3) participants are categorized as being aware or unaware of stimulus contingencies overall and that this is then entered as a between-subjects variable in the analysis, hence crucial awareness measurements for specific stimulus pairs are not taken into account. These criticisms were addressed in Hammerl's response (Hammerl, 2000), who pointed out that (1) contrary to Field's claim, several studies have used random stimulus assignment and have observed evaluative learning (e.g., Baeyens, Eelen, Hammerl, Bloch, & Silverthorne, 1997;Hammerl & Grabitz, 1993, 1996Todrank, Byrnes, Wrzesniewski, & Rozin, 1995), and (2) that although all previous studies have used a withinsubjects control, when a between-subjects control is in place, evaluative learning is still observed .…”
mentioning
confidence: 99%
“…This relates to the role of awareness in learning. Field (2000a) draws a useful distinction between two types of awareness. The extent to which a person acquires cognizance that a particular CS has previously preceded a particular US can be called contingency awareness.…”
Section: Introductionmentioning
confidence: 99%